Artificial Intelligence (AI) for Information Services Delivery by Librarians in Universities in Northwest Nigeria: Case Study of Kashim Ibrahim Library, Ahmadu Bello University, Zaria - Sadiat Lola Atte (Journal of Information Systems and Technology, 2025)
Artificial Intelligence (AI) is revolutionizing library services globally by automating processes, enhancing user engagement, and improving information retrieval efficiency. This study evaluates AI integration for information service delivery at Kashim Ibrahim Library, Ahmadu Bello University, Zaria, Northwest Nigeria, a region with limited AI adoption in academic libraries. The population comprised 90 academic librarians. Research objectives were to identify AI technologies librarians are aware of and determine challenges hindering integration. A descriptive survey design employed a structured questionnaire with a 4-point Likert scale (Strongly Agree=4, Agree=3, Disagree=2, Strongly Disagree=1). Validity was ensured through expert review, and reliability via Guttman Split-half test (r=0.91). Data from 90 respondents were analyzed using mean (x̄) and standard deviation (σ), benchmarked against a decision mean of 2.50. Findings from the study revealed high awareness of chatbots (x̄=3.25) and recommendation systems (x̄=3.10), moderate for automated cataloging (x̄=2.70) and NLP (x̄=2.60), but low for text mining (x̄=2.15). Major challenges included insufficient funding (x̄=3.40), lack of trained personnel (x̄=3.20), and unreliable infrastructure (x̄=2.90). The study concludes that AI awareness exists but integration is constrained by resource and skill deficits.